A laboratory of transnational history : Ukraine and recent Ukrainian historiography - Kasʹi͡anov, H. V. (Heorhiĭ Volodymyrovych), 1961-; Ther, Philipp (Central European University Press, 2009)
A first attempt to present an approach to Ukrainian history which goes beyond the standard 'national narrative' schemes, predominant in the majority of post-Soviet countries after 1991, in the years of implementing 'nation-building projects'. An unrivalled collection of essays by the finest scholars in the field from Ukraine, Russia, USA, Germany, Austria and Canada, superbly written to a high academic standard. The various chapters are methodologically innovative and thought-provoking. The biggest Eastern European country has ancient roots but also the birth pangs of a new autonomous state. Its historiography is characterized by animated debates, in which this book takes a definite stance. The history of Ukraine is not written here as a linear, teleological narrative of ethnic Ukrainians but as a multicultural, multidimensional history of a diversity of cultures, religious denominations, languages, ethical norms, and historical experience. It is not presented as causal explanation of 'what has to have happened' but rather as conjunctures and contingencies, disruptions, and episodes of 'lack of history.'